Петровские ассамблеи как социокультурное явление в начале XVIII века - Романюта, Л.А. (Культура народов Причерноморья, 2013)
Бал в истории русской культуры XVIII века был регламентированной формой светской
жизни. Начало русским балам было положено при Петре I Указом об ассамблеях. Основным социальным
значением ассамблей петровского времени являлась выработка в обществе потребности к публичному
проведению досуга, формирование интереса к светской жизни, патриотизма, а также нравов русского
общества. После смерти Петра I ассамблеи прекратили свое существование, но балы заняли твердые
позиции в культурной жизни Российской империи.
Ключевые слова: культура, искусство, бал, петровские ассамблеи, историко-бытовой танец. Бал в історії російської культури XVIII століття був регламентованою формою світського
життя, він був покликаний визначити тип соціальної поведінки всередині дворянської культури.
Початок російським балам було покладено за часів Петра I Указом про асамблеї. Основним соціальним
значенням асамблей петровського часу було вироблення в суспільстві потреби до публічного проведення
дозвілля, формування інтересу до світського життя, патріотизму, а також моралі російського
суспільства. Після смерті Петра I асамблеї припинили своє існування, але бали зайняли міцні позиції в
культурному житті Російської імперії.
Ключові слова: культура, мистецтво, бал, петровські асамблеї, історико-побутовий танець. Dance party in the history of Russian culture of the XVIII century was regulated form of social life, it
was called upon to determine the type of social behaviour within the nobility’s culture. The beginning of Russian
dance parties were put under Peter I by the Decree of the assemblies. Peter I tried to bring together the Russian
estate through public holidays, which served as a pretext for the success of the Russian army during this period.
It was emphasized that in the assemblies, women should participate equally with men. At the beginning of the
XVIII century Peter’s Assemblies should have done the same tasks that are actual today. Dances started with
staid Polish, then followed the minuet, they were the ceremonial dances. Сeremonial’s dances were changed by
dancing- games, comic dancing, fast and fun - ketten-dance, ekosez, as well as grosfater dance that Peter I
performed. The other group consisted of English dances - anglez, allemand and contrdance. Peter’s Assemblies
were often ended with fireworks, which were based on political themes. Dancing was a very big examinig to the
Assembly. They were held, bad move in unusual costumes. Peter’s assemblies were neither sophisticated
atmosphere or trained manners. After Peter I‘s death the assemblies were stopped existing, but the dances had
taken a strong position in the cultural life of the Russian society. In the second quarter of the XVIII century there was a
gradual development of culture of the dances in Russia. The ability to dance helped the growing the career,
because dancing was considered to be an important advantage and could bring sucess not only in the ballroom.
Basic social value of Peter's Assemblies was to make out in the community the needs to public leisure activities,
the formation of interest in the social life, patriotism and morals of Russian society. The participation in the
Assembly for the higher ranks of Russian society at the time of Peter I was forced, but could to cultivate in the
socio-cultural environment and grow in an era of balls when the ball had become very popular in the community
and had a special social functions.
Keywords: art, dance, ballroom dance, Peter Assembly, historical-social dance.